Effect of the ironing process on ABS parts produced by FDM. Issue 2 (4th February 2020) - Sardinha, Manuel; Vicente, Carlos M.S.; Frutuoso, Nuno; Leite, Marco; Ribeiro, Relógio; Reis, Luís
Abstract: In this work, the effect of a thermal process termed ironing on the superficial, mechanical, and dimensional properties of Acrylonitrile Butadiene Styrene (ABS) parts produced by fused deposition modelling (FDM) is evaluated. Three sets of samples for each studied parameter were manufactured. Cubic samples were used to evaluate the influence of the process in the average surface roughness ( Ra ) of top layers. Prismatic beams and plates were chosen to evaluate the interlaminar strength (ILS) and warping of parts, respectively. A Python script was developed to enhance the applicability of process. Although ironing may influence the thermal behaviour of deposited layers, it was not effective in enhancing the ILS of parts, due to the generation of geometric irregularities. The results show that ironing can reduce the Ra of ABS parts up to 60% and distortion levels by 33%. The study suggests ironing as an alternative postprocessing technique for FDM parts.